2017
DOI: 10.1016/j.hedp.2017.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Soft x-ray induced femtosecond solid-to-solid phase transition

Abstract: Soft x-rays were applied to induce graphitization of diamond through a non-thermal solid-tosolid phase transition. This process was observed within poly-crystalline diamond with a timeresolved experiment using ultrashort soft x-ray pulses of duration 52.5 fs and cross correlated by an optical pulse of duration 32.8 fs. This scheme enabled for the first time the measurement of a phase transition on a timescale of ~150 fs. Excellent agreement between experiment and theoretical predictions was found, using a dedi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 33 publications
(13 reference statements)
1
35
0
Order By: Relevance
“…[22], and the timeresolved kinetics of a phase transition in Ref. [23], which also validated our calculations of the optical parameters; damage thresholds in amorphous carbon and C 60 crystal were compared to experiments in Ref. [24].…”
Section: Modelsupporting
confidence: 69%
See 1 more Smart Citation
“…[22], and the timeresolved kinetics of a phase transition in Ref. [23], which also validated our calculations of the optical parameters; damage thresholds in amorphous carbon and C 60 crystal were compared to experiments in Ref. [24].…”
Section: Modelsupporting
confidence: 69%
“…Electrons, promoted across the band gap under an action of a laser pulse, populate those states, causing the materials to turn into an LDL phase. In contrast, other materials do not exhibit an LDL phase: diamond with 2p bonds graphitizes [22,23] and GaP and GaSb with 4p bonds forming the conduction band (see Fig. 8) turn into a completely disordered lowdensity phase.…”
Section: Discussionmentioning
confidence: 99%
“…In a series of papers, we modeled diamond under femtosecond FEL irradiation in a wide range of photon energies, using XTANT code described above 10,13,60,69,94 . We showed that at the absorbed doses above the damage threshold of ∼ 0.7 − 0.75 eV/atom, diamond undergoes a nonthermal solid-to-solid phase transition into graphite phase on an ultrashort timescale of ∼ 150 fs.…”
Section: Nonthermal Graphitization Of Diamondmentioning
confidence: 99%
“…It should also be mentioned that the data quality and the ability to resolve fine features of the signal, demonstrated, for example, by Fig. 2, significantly exceed those typical for time-resolved EUV pump/optical probe measurements, [15][16][17] indicating the advantage of the background-free TG experiment, in which the diffracted optical signal vanishes in the absence of the EUV excitation. Our results indicate the promise of the TG technique for studying a wide range of phenomena initiated by femtosecond EUV pulses.…”
mentioning
confidence: 90%
“…High brightness EUV and x-ray free electron lasers (FELs) now allow experiments in which femtosecond short-wavelength pulses are used to initiate dynamics probed with optical or short-wavelength radiation. [11][12][13][14][15][16][17] This report is aimed at exploring the potential of short-wavelength photon pulses for the excitation of lattice vibrations.…”
mentioning
confidence: 99%